THE CHANGE OF QUALITY OF SPRING SOFT WHEAT GRAIN DURING THE BREEDING - V. G. Zakharov; O. D. Yakovleva (Зерновое хозяйство России, 2018)
The article has presented the study results of grain quality of 14 spring soft wheat varieties as a variety change of the crop in the Ulyanovsk region. It has been shown that during the 60-year period the productivity increased on 1.02 t/ha due to zonation of the variety ‘Lyutestcens62’ and it had been increasing on 0.22 t/ha at each new stage of the variety change. In contrast to the productivity, the change of the grain qualitative indexes has a different tendency. It has been noted the increase of all physical indexes of grain quality, first of all 1000-kernel weight, which increased on 0.9 g as a result of breeding. The results of the correlation analysis showed that 1000-kernel weight has got a positive correlation with the kernels productivity (r=0.69**), uniformity (r=0.70**) and volume of bread (r=0.50). The content of protein and gluten tends to decrease. The difference in the content of protein among the varieties of the first and the sixth stages was 1.3%; the difference in the content of gluten was 3.3%. During the stages of the variety change the content of protein decreased on 0.25%, gluten on 0.27% without improvement of its quality. With the increase of the potential of new variety productivity the gross yield of protein and gluten per unit of square increases. The correlation analysis established a significant negative connection of the content of protein with productivity (r=-0.76*) and 1000-kernel weight (r=-0.55***). Due to the variety changes there is an improvement of volume of bread and general baking valuation. Among the varieties of different periods of the variety change, there have been found the varieties with high biochemical and baking traits.